Single-event Transient (SET) effects on 60nm and 32nm 3T CMOS active pixel sensor - Ahamad Sukor, Masturah; Hasbullah, Nurul Fadzlin; Ibrahim, Siti Noorjannah (Penerbit UMT, Universiti Malaysia Terengganu (UMT), 2016)
Nowadays, CMOS Active Pixel Sensors (APS) are widely used especially in space mission. However, the space consists of various kind of radiation. Single-Event Transient (SET) is one of the concern for the circuits in the radiation environment. SETs are becoming a common phenomenon with technology scaling due to lower operating voltage and smaller nodal capacitance. A 60nm and 32nm PTM technology of 3T CMOS APS have been designed and simulated using Silvaco Gateway and exposed to a broad Linear Energy Transfer (LET) range to investigate the effects of SET towards downscaling of 3T CMOS APS and to observe the critical Linear Energy Transfer (LET) for each technology. The output current and voltages obtained for each simulation shows the effect of LET towards the performance of 3T CMOS APS. Varying the LET towards the same technology shows how huge the impact of LET towards the drain current of affected node. Then, we identify the critical LET for each technology. The SET effect is shown through the charge collection at different value of LET. Even though the effect of SET is momentary, it may propagate throughout the circuit and consequently cause the Single Event Upset (SEU) in memory devices.